2020
DOI: 10.1016/j.tmrv.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Platelet Responses in Transfusion-Related Acute Lung Injury (TRALI)

Abstract: Platelets are versatile cells which are capable of eliciting non-hemostatic immune functions, especially under inflammatory conditions. Depending on the specific setting, platelets may be either protective or pathogenic in acute lung injury and Acute respiratory distress syndrome (ARDS). Their role in Transfusion-related acute lung injury (TRALI) is less well defined, however, it has been hypothesized that recipient platelets and transfused platelets both play a pathogenic role in TRALI. Overall, despite confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…We and others have previously reported that, in WT mice, monocytes/macrophages are essential to induce TRALI with the mouse IgG2a anti-MHC I mAb 34-1-2S 7,12,13,15 , while neutrophils and platelets are dispensable 7,8,11,12 . Controversies have long existed, however, especially regarding the contribution of the recipient platelets to the pathology, notwithstanding the recent consensus that platelets may not be critically required for the onset and development of TRALI in WT mice 36, 37 . Here, similar cell-dependent features were observed in CD32Aanimals when TRALI was induced by the chimera hIgG1-34-1-2S.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported that, in WT mice, monocytes/macrophages are essential to induce TRALI with the mouse IgG2a anti-MHC I mAb 34-1-2S 7,12,13,15 , while neutrophils and platelets are dispensable 7,8,11,12 . Controversies have long existed, however, especially regarding the contribution of the recipient platelets to the pathology, notwithstanding the recent consensus that platelets may not be critically required for the onset and development of TRALI in WT mice 36, 37 . Here, similar cell-dependent features were observed in CD32Aanimals when TRALI was induced by the chimera hIgG1-34-1-2S.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly believed that antibody-mediated TRALI is the result of pulmonary damage caused by neutrophils. However, the pathogenic role of other cells, including monocytes, macrophages, endothelial cells and platelets have been well studied (1,14,15,(34)(35)(36)(37). Nevertheless, these cellular pathways remain complex and somehow depend on antibody specificities (1).…”
Section: Discussionmentioning
confidence: 99%
“…In the classical antibody-mediated TRALI model, neutrophils have been implicated as important factors (9)(10)(11), while other studies have reported that monocytes and macrophages, rather than neutrophils, play crucial roles in the development of TRALI (12,13). Significant controversy, however, still exists concerning the role of platelets in TRALI (14). Recent studies in murine models have demonstrated that osteopontin, secreted by macrophages, was critically required for TRALI induction via stimulation of neutrophil-recruitment into the lungs (15), and that Fc-mediated complement activation was an important feature of TRALI (16).…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, estudios sugieren que las plaquetas presentes tanto en el receptor como en el donador pueden tener un papel patogénico en los cuadros de daño pulmonar, incluido TRALI o en SDRA, sin embargo, su participación es limitada (28).…”
Section: Fisiopatologíaunclassified